Proposals for Cleaning and Lighting the City of Edinburgh (with original signatures of a number of the principal inhabitants), in the year 1735, With Explanatory Remarks (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author regretfully acknowledges the sanitary issues present in Edinburgh from the sixteenth to the eighteenth century, as well as the various methods the city council attempted to solve these problems. The document referenced in the title was one of these methods, intended to stop residents of Edinburgh throwing their waste out the window by offering them the opportunity to pay someone to carry it down the stairs for them. The proposal also mentions the names and residences of the people who agreed to the scheme. The author concludes with a short summary of the public works proposed by the man he argues is the author of this document – Robert Mein.